Crowdfunding information : a voluntary contributions experiment, through a discrete-choice based mechanism (2017)
When a private, non-profit organization produces information to be found freely on the internet, it is not only supplying this good at a suboptimal level, but, during its production, it is incurring in high private costs that lead to financing issues. This paper reports a discrete choice experiment conducted to explore if voluntary donations through crowdfunding is a viable financing mechanism for these kinds of organizations. The experiment tries to understand the factors that lead to a change in the probability an agent will donate through the mentioned crowdfunding mechanism. Results indicate there are factors such as matching grants which act as effective mechanisms for increasing the probability an individual will contribute towards these organizations in a hypothetical donation situation. Willingness to Pay measures (WTP) for the inclusion of this attribute are estimated to be around COP43,000. Additionally, there are factors such as costs, represented in the donation value and in the frequency a donation campaign will occur, which decrease the probability an individual will donate, resulting in welfare loss of close to COP17,000 in the case of the frequency of donation attribute.